FCNC decays of spin-1/2 double heavy baryons to spin-3/2 single heavy baryons - Aliev Tahmasib; Askan Emre; Ozpineci Altug; Sarac Yasemin (EPJ Web of Conferences, 2024)
In recent years, there have been many discoveries in the spectroscopy of hadrons containing heavy quarks. Almost all baryons containing a single heavy quark are discovered in experiments. The quark model predicts the existence of many baryons with double heavy quarks. Among the possible double heavy baryons, only Ξ+cc and Ξ+cc have been experimentally observed in LHCb. Flavor-changing neutral current (FCNC) processes represent a promising platform for precise testing of SM and looking for new physics beyond the SM. In this study, the weak decays of spin-1/2 double heavy baryons to spin- 3/2 single heavy baryons induced by FCNC are studied within the light cone QCD sum rules method. First, the transition form factors of Ξ0,-bb → Ξ*,0,-b ‾ll, Ξ0,-bb → Ξ*,0,-b ‾ll, Ω-bb → Ξ*-b ‾ll, Ω-bb → Ξ*-b ‾ll decays are calculated. Then, the corresponding decay widths are estimated using the results for the form factors.